The feasibility of endourological surgery in low‐resource settings. (3rd June 2022) - Watson, Graham; Niang, Lamine; Chandresekhar, Srinath; Natchagande, Gilles; Payne, Stephen R.
Abstract : One of the widest variations in contemporary surgical practice between high and low, or low‐middle, income countries is the utilisation of endoscopy as a means of treating urological pathology. The endoscopic management of lower urinary tract problems such as benign prostatic hypertrophy, bladder cancer and urethral strictures was established in the UK in the late 1970s, whilst its adoption into everyday practice in sub‐Saharan Africa (SSA) has been significantly retarded. It is still neither a major feature of urological training in those countries nor widely available to the patients that established consultants treat. Likewise, the explosion of less invasive technologies for treating upper tract stone disease in the 1980s, particularly the management of renal stone disease, has also lagged behind practice established in the UK over the last 40 years. This is not due to a lack of patients who could be treated endoscopically or restricted by the abilities of the surgeons in SSA. The restraint in assumption of these less‐invasive management options is rather due to the physical availability of trained specialist surgeons, their access to basic infrastructure such as electricity and water, access to endoscopes and the peripheral equipment necessary to successfully deploy them, and the ability of patients to afford the disposable items required for less‐invasive forms of management. Some endoscopic procedures are viable in resource‐poor settings. However, they are largely dependent upon the supply of equipment from non‐governmental organisations in high‐income countries, frugal innovation to reduce individual procedure costs, adequately skilled mentors, and maintenance and supply chains to make them a durable option in patient management. Urolink and the Medi Tech Trust present their experience of how endoscopic surgery can be taught, and used sustainably, in a resource‐poor healthcare environment.